2016
DOI: 10.1038/srep38004
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting High Dynamin-2 (DNM2) Expression by Restoring Ikaros Function in Acute Lymphoblastic Leukemia

Abstract: Dynamin-2 (DNM2) is a GTPase essential for intracellular vesicle formation and trafficking, cytokinesis and receptor endocytosis. Mutations in DNM2 are common in early T-cell precursor acute lymphoblastic leukemia. However, DNM2 expression in other types of ALL are not reported. We studied DNM2 mRNA level in adults with B- and T-cell ALL. We found DNM2 is more highly expressed compared with normals in both forms of ALL. High DNM2 expression is associated with some clinical and laboratory features, inferior out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Similarly, together with Cav-1, DNM2 also mediates effects on cancer formation and progression. The 2 proteins are involved in the endocytosis of a number of receptor proteins, ligands and signaling molecules (19,62). However, it has been suggested that there are several other interlinked signaling pathways that, in response to overexpression of Cav-1 and DNM2, may be activated and/or deactivated, resulting in tumor formation (63).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, together with Cav-1, DNM2 also mediates effects on cancer formation and progression. The 2 proteins are involved in the endocytosis of a number of receptor proteins, ligands and signaling molecules (19,62). However, it has been suggested that there are several other interlinked signaling pathways that, in response to overexpression of Cav-1 and DNM2, may be activated and/or deactivated, resulting in tumor formation (63).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent work confirmed the presence of the CK2-Ikaros signaling axis, and its role in regulating expression of a large number of tumor promoters and suppressors in pediatric and adult leukemia (Ge et al, 2015, 2016a, 2016b, 2016c, 2016d, 2017; Wang et al, 2016). Epigenetic analysis of the promoters of Ikaros target genes showed that CK2 regulates not only Ikaros DNA-binding affinity to promoters of its target genes, but also Ikaros-mediated recruitment of HDAC1, as well as the epigenetic signature at regulatory elements of Ikaros targets (Song et al, 2016).…”
Section: Ikzf1 (Ikaros)mentioning
confidence: 80%
“…Ikaros binding to the promoter of DNM2 was observed in both B-ALL and T-ALL cells [108]. Overexpression of Ikaros in both types of leukemia resulted in reduced transcription of DNM2.…”
Section: Dynamin 2 (Dnm2)mentioning
confidence: 96%
“…The DNM2 protein has five domains: GTPase domain; intermediate domain (MD); pleckstrin homology domain (PH); GTPase effector domain (GED); and proline-arginine-rich domain (PRD). Recurrent mutations in all DNM2 domains including the GTPase domain have been linked to T-ALL [105][106][107][108][109]. It has been suggested that DNM2 plays a major role in the internalization of IL7R, TCR, and Notch ligand Delta like 1 (DIl-1), thereby triggering the development of ALL [110].…”
Section: Dynamin 2 (Dnm2)mentioning
confidence: 99%